2013
DOI: 10.1104/pp.113.215970
|View full text |Cite
|
Sign up to set email alerts
|

Serine Acts as a Metabolic Signal for the Transcriptional Control of Photorespiration-Related Genes in Arabidopsis  

Abstract: Photosynthetic carbon assimilation including photorespiration is dynamically regulated during the day/night cycle. This includes transcriptional regulation, such as the light induction of corresponding genes, but little is known about the contribution of photorespiratory metabolites to the regulation of gene expression. Here, we examined diurnal changes in the levels of photorespiratory metabolites, of enzymes of the photorespiratory carbon cycle, and of corresponding transcripts in wild-type plants of Arabido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
58
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 58 publications
10
58
0
1
Order By: Relevance
“…It would also be of interest to test how transcriptomic changes in protein metabolism are reflected in the rate of protein synthesis of the cell. In our study, the accumulation of Ser and Gly to high levels at early time points of infection may be related to the transcriptional repression of photorespiration that we observed (Timm et al, 2013). Indeed, higher accumulation of the photorespiratory intermediates Ser and Gly is known to cause a feedback deregulation of photorespiration-related genes (Timm et al, 2013).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…It would also be of interest to test how transcriptomic changes in protein metabolism are reflected in the rate of protein synthesis of the cell. In our study, the accumulation of Ser and Gly to high levels at early time points of infection may be related to the transcriptional repression of photorespiration that we observed (Timm et al, 2013). Indeed, higher accumulation of the photorespiratory intermediates Ser and Gly is known to cause a feedback deregulation of photorespiration-related genes (Timm et al, 2013).…”
Section: Discussionsupporting
confidence: 50%
“…In our study, the accumulation of Ser and Gly to high levels at early time points of infection may be related to the transcriptional repression of photorespiration that we observed (Timm et al, 2013). Indeed, higher accumulation of the photorespiratory intermediates Ser and Gly is known to cause a feedback deregulation of photorespiration-related genes (Timm et al, 2013). The accumulation of several other amino acids could reveal antiviral responses in infected leaves.…”
Section: Discussionsupporting
confidence: 49%
“…Thus, Ser could well be the link connecting primary metabolism with the control of cell cycle progression in specific cell types. This could be related to the role of Ser in transcriptional regulation (Timm et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Serine is involved in the biosynthesis of purines and pyrimidines, and serves as an important precursor for other essential compounds, including the amino acids glycine and cysteine or phospholipids (Walton & Woolhouse, 1986). Recently, it has been shown that serine also acts as a metabolic signal for the transcriptional regulation of photorespiratory genes in the model plant Arabidopsis thaliana (Timm et al, 2013).…”
Section: Introductionmentioning
confidence: 99%